2018
DOI: 10.1055/a-0639-5147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic papillary large balloon dilation with or without endoscopic sphincterotomy for the treatment of large bile duct stones

Abstract: Background Endoscopic papillary large balloon dilation (EPLBD) without prior endoscopic sphincterotomy (EST) produces excellent outcomes for the treatment of large common bile duct (CBD) stones. However, it remains unclear how the outcomes of EPLBD alone compare with those of EPLBD with EST. In this study, we assessed the safety and therapeutic outcomes of EPLBD with vs. without EST for the removal of large bile duct stones. Methods This prospective, multicenter study was conducted on 200 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 33 publications
(39 reference statements)
2
36
0
4
Order By: Relevance
“…Dies ist vor allem für die Entwicklung von Steinrezidiven, die sich bei Patienten mit Steinextraktion nach Bal-londilatation beinahe halbiert, signifikant. Bei der kombinierten Behandlung von Gallengangsteinen > 10 mm mit Ballondilatation nach vorheriger EPT zeigte sich: Bei vergleichbarer Erfolgsrate waren sowohl das Pankreatitis-Risiko als auch die Blutungsrate im Vergleich zur alleinigen EPT nicht erhöht [55,56].…”
Section: Erc Mit Endoskopischer Ballondilatationunclassified
“…Dies ist vor allem für die Entwicklung von Steinrezidiven, die sich bei Patienten mit Steinextraktion nach Bal-londilatation beinahe halbiert, signifikant. Bei der kombinierten Behandlung von Gallengangsteinen > 10 mm mit Ballondilatation nach vorheriger EPT zeigte sich: Bei vergleichbarer Erfolgsrate waren sowohl das Pankreatitis-Risiko als auch die Blutungsrate im Vergleich zur alleinigen EPT nicht erhöht [55,56].…”
Section: Erc Mit Endoskopischer Ballondilatationunclassified
“…It was believed that an EST before EPLBD may prevent post‐procedural pancreatitis because the radial force produced by balloon dilation is shifting along the EST direction rather than pancreatic duct direction . However, many studies have reported that EPLBD without a preceding EST is as effective and safe for difficult bile duct stone removal without increasing the risk of pancreatitis …”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, many studies have reported that EPLBD without a preceding EST is as effective and safe for difficult bile duct stone removal without increasing the risk of pancreatitis. 8,9 In early EPLBD trials, the balloon dilation of the biliary orifice was extended up to a diameter of 20 mm, whereas today, balloons with diameters > 15 mm tend to be less frequently used than in the earlier days because of concerns about potential perforations or bleeding. However, there has been limited data regarding the frequency of severe-to-fatal adverse events during EPLBD using larger balloons (> 15 mm).…”
Section: Introductionmentioning
confidence: 99%
“…The design of the RCT by Kogure et al did not intend to compare EPLBD with or without the use of EST. In this journal last year, Park et al [5] randomized 200 patients with bile duct stones > 10 mm in size to receive EPLBD alone or EPLBD with EST. The overall adverse event rates were low (6 vs. 4 %) and the pancreatitis rates were 1 % vs. 3 %, respectively.…”
mentioning
confidence: 99%